Case report: Avoidant/restrictive food intake disorder after tonsillectomy - Ahmed, Gellan K.; Karim, Ahmed A.; Khedr, Eman M.; Elbeh, Khaled; Moheb, Amira; Abokresha, Marwa; Haridy, Nourelhoda A. (Frontiers in Psychiatry, 2024)
Background: Avoidant Restrictive Food Intake Disorder (ARFID) is a newly classified eating disorder that requires further understanding of its presentation. There is no previous report of ARFID in a child post-tonsillectomy. ARFID may be a potential negative outcome for children following oropharyngeal surgery.Case presentation: a female child aged 10 years and 2 months presented with ARFID associated with depression, anxiety and nutritional deficiency following tonsillectomy. She had more difficulty in swallowing solids than fluids and had repeated vomiting and spitting food after chewing it. She became dehydrated and malnourished with a BMI of 10.5 and was misdiagnosed with myasthenic gravis.To our knowledge, this is the first case report of ARFID in a child posttonsillectomy. We discuss the pathophysiology of ARFID, which remains elusive, and recommend psychiatric assessment when evaluating children post operative tonsillectomy.